The effect of antifungal activities of auto-polymerized silicone soft denture liner material containing origanum vulgare gel against Candida albicans over 14-day period: an in vitro study - Ariyani, Ariyani; Nasution, Ismet Danial; Suryanto, Dwi; Gea, Saharman; Abdul Rahman, Syarifah Nur Syed; Binti Awang, Khalijah (Universitas Padjadjaran, 2025)
ABSTRACT Introduction: The greatest disadvantage of silicone soft denture liner (SDL) materials is the difficulty in keeping them clean due to their incompatibility with conventional denture cleaning solutions. As a result, chemical methods are often recommended as effective alternatives to mechanical cleaning. Natural products have emerged as promising substitutes for synthetic chemical agents. Origanum vulgare, in particular, has shown significant antifungal activity against Candida albicans. This study aims to analyze the effect of antifungal activities of auto-polymerized silicone soft denture liner material containing Origanum vulgare gel against Candida albicans over a 14 days period. Methods: The antifungal activity was evaluated using the disc diffusion method. The samples were divided into three groups: (1) SDL without antifungal agent addition, (2) SDL with nystatin addition, and (3) SDL with Origanum vulgare gel addition. Data were analyzed using one-way ANOVA and Dunnett’s T3 for usage duration of 7 and 14 days. Results: The addition of Origanum vulgare gel showed significant antifungal activity, with minimum inhibitory concentration (MIC) 3.12% and minimum fungicidal concentration (MFC) 6.25%. One way ANOVA analyses the inhibition zone of Candida albicans was significantly affected by the usage duration (7 and 14 days), with p<0.001 respectively. Post-hoc analyses using Dunnett's T3 test for the groups at 7 days and 14 days revealed significant difference in the antifungal effect between each group with MIC and MFC. Conclusion: Nystatin was found to be less effective than Origanum vulgare gel in inhibiting the growth of C. albicans. The addition of Origanum vulgare gel at a concentration of 6.25% to auto-polymerized silicone SDL is recommended, as it effectively inhibits the growth of Candida albicans for up to 14 days.KEYWORDS Soft denture, essential oil, Origanum vulgare, inhibition zone, Candida albicans